Synthesis and biological activities of some novel aminomethyl derivatives of 4-substituted-5-(2-thienyl)-2,4-dihydro-3H-1,2,4-triazole-3-thiones - Koparir, Metin; Orek, Cahit; Parlak, Akif Evren; Soylemez, Abdurrazak; Koparir, Pelin; Karatepe, Mustafa; Dastan, Sevgi Durna (Elsevier France-Editions Scientifiques Medicales Elsevier, 2013)
A novel series of compounds were synthesized by cyclic condensation reaction of substituted isothiocyanate (2a-c) with 2-thiophenecarboxylic acid hydrazide (1) in the presence of ethyl alcohol, to obtain intermediate thiosemicarbazides (3a-c), which were further treated with sodium hydroxide in the presence of ethanol to obtain triazole derivatives (4a-c). The latter were refluxed with substituted secondary amines and formaldehyde for 6-10 h to afford Mannich bases (5a-k). The synthesized compounds were characterized on the basis of their spectral (IR, C-13 and H-1 NMR) data and evaluated for biological activities. Some of the compounds were found to exhibit significant antimicrobial and antioxidant activity. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: 4-Substituted-5-(2-thienyl)-2,4-dihydro-3H-1,2,4-triazole-3-thiones; Mannich bases; Biological activity